Civil-legal status of a foreign legal entity in Private International Law: a comparative legal analysis - Nukusheva, А.А.; Kudryavtseva, L.V. (Publ.KarSU, 2017)
The article regards the issues of determining the civil status of the foreign legal entities that act as the main participants in investment activity in the territory of the host state. The problem of determining the personal status of a legal entity in private international law is due to fact that economic activity of legal entities more often goes beyond the borders of one state and often covers many other states. The participation of legal entities in international civil law relations raises a number of legal issues, primarily related to the legal status of a foreign legal entity. One of the first questions arising when a foreign legal entity is admitted to the territory of the host state is whether a legal entity established under the laws of one state is considered to be a legal entity in a foreign state where it is planning to operate? Based on the analysis of the national legislation of the Republic of Kazakhstan, the Russian Federation and the bilateral treaties on the promotion and protection of investments, various approaches have been identified to determine the nationality of a legal entity. Various points of view, existing in the legal literature, regarding the legal status of foreign legal entities in private international law are considered. The comparative characteristics of the category of «personal law of a legal entity » are fixed in the civil legislation of the Republic of Kazakhstan, the Russian Federation and bilateral treaties on the promotion and protection of investments. The comprehensive analysis of the legislation allowed the authors to conclude that a unified approach is taken in the choice of the «nationality» criterion of a legal entity in Kazakhstan and Russian legislation systems, these are the criteria for the establishment or registration of a legal entity (incorporation theory).
Халықаралық жеке құқықтағы шетел заңды тұлғаларының азаматтық- құқықтық мəртебесі: салыстырмалы-құқықтық талдау
Гражданско-правовой статус иностранного юридического лица в международном частном праве: сравнительно-правовой анализ
Keywords: civil and legal status of investors; a private law of the legal entity; the nationality of the legal entity; the statute of the legal entity; bilateral treaty on promotion and protection of investments; a treaty on promotion and mutual protection of investments; a doctrine of the nationality of the legal entity